Pressure Calibration of Large-Volume Press: A Case Study of Hinged 6-8 Type Large-Volume High-Pressure Apparatus - Ren, Dongsheng; Li, Heping (Frontiers in Earth Science, 2022)
In this study, methods for the pressure calibration of 6-8 static high-pressure apparatus were investigated. The relationship between the pressure of DS 6×1400 t pressing oil and the chamber pressure was calibrated using water, ZnTe, ZnS, and GaAs at room temperature. Also, the relationship between the pressure of the DS 6×1400 t pressing oil and the chamber pressure was calibrated by the phase transition experiments using KCl, LiCl, KCl + LiCl, and quartz-coesite at high temperatures. We found a linear relationship between the cavity pressure and the oil pressure at room temperature. However, when the temperature and pressure increased to certain values, the chamber pressure and the oil pressure deviated from the linear relationship.